2012
DOI: 10.1902/jop.2012.110585
|View full text |Cite
|
Sign up to set email alerts
|

The Gingival Crevicular Fluid Levels of Interleukin‐11 and Interleukin‐17 in Patients With Aggressive Periodontitis

Abstract: The IL-11/IL-17 ratio was decreased in the GAgP group because of the decreased IL-11 levels. The IL-11/IL-17 axis and the link between IL-17 and neutrophil function disorders in AgP should be investigated to clarify the role of the IL-11/IL-17 axis and its balance and imbalance in the pathogenesis of AgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…In most studies on IL‐17 and/or IL‐23, only one diseased group, consisting of patients with advanced periodontitis, has been compared with control group. GCF 43 , 44 or gingival tissue biopsies 45 , 46 have been generally used as study specimens. In a study by Lester et al, 45 a moderate periodontitis group was also included, and authors found increased IL‐17A concentrations with progression of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies on IL‐17 and/or IL‐23, only one diseased group, consisting of patients with advanced periodontitis, has been compared with control group. GCF 43 , 44 or gingival tissue biopsies 45 , 46 have been generally used as study specimens. In a study by Lester et al, 45 a moderate periodontitis group was also included, and authors found increased IL‐17A concentrations with progression of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, overproduction of cytokines from chronic TLR stimulation leads to destruction of tissue. In gingival fibroblasts, cytokines promote the synthesis of IL-8, IL-1β, IL-10, and prostaglandin E2 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Ay et al (25) reported that the total amount of IL-17 in GCF from aggressive periodontitis was significantly higher than that of the healthy group. Yamaguchi et al (26) demonstrated that the immunoreactivity for Th17, IL-17, IL-17R, RANKL and RANK in the rheumatoid arthritis model mice was significantly higher in the PDL tissue subjected to orthodontic force on day 9 when compared with the normal healthy group.…”
Section: Discussionmentioning
confidence: 97%